2016
DOI: 10.3389/fimmu.2016.00629
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of Type I Interferons in Differentiation and Activation of Tumor-Associated Neutrophils

Abstract: Type I interferons (IFNs) were first characterized in the process of viral interference. However, since then, IFNs are found to be involved in a wide range of biological processes. In the mouse, type I IFNs comprise a large family of cytokines. At least 12 IFN-α and one IFN-β can be found and they all signal through the same receptor (IFNAR). A hierarchy of expression has been established for type I IFNs, where IFN-β is induced first and it activates in a paracrine and autocrine fashion a cascade of other type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 151 publications
5
67
0
1
Order By: Relevance
“…MYC-driven lymphomagenesis 148 significantly increased numbers of pan CD11c + DCs and neutrophils (Supplementary Figures 149 4d-e). The increase in numbers of DCs and neutrophils during MYC-driven lymphomagenesis 150 corroborated the previously well-characterized pro-tumorigenic functions of these subsets in 151 lymphomas [18][19][20] . 152…”
Section: Immune Composition Of Myc-driven Lymphomas Is Altered Indepesupporting
confidence: 72%
“…MYC-driven lymphomagenesis 148 significantly increased numbers of pan CD11c + DCs and neutrophils (Supplementary Figures 149 4d-e). The increase in numbers of DCs and neutrophils during MYC-driven lymphomagenesis 150 corroborated the previously well-characterized pro-tumorigenic functions of these subsets in 151 lymphomas [18][19][20] . 152…”
Section: Immune Composition Of Myc-driven Lymphomas Is Altered Indepesupporting
confidence: 72%
“…As a result, IFN-mediated homeostasis must be very tightly regulated, as prolonged or aberrant exposure is deleterious. Perturbations of IFN expression or signaling contribute to the etiology of several autoimmune diseases, dysregulated antiviral responses, and cancer (Corrales et al, 2017; Crow and Manel, 2015; Davidson et al, 2014; Pylaeva et al, 2016; Wilson et al, 2013). Many of these pathological conditions arise when PRRs inappropriately sense endogenous nucleic acids and it is now clear that aberrant nucleic acid metabolism and DNA damage are responsible for a multitude of autoimmune diseases (Crowl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TANs survive longer than circulating neutrophils that allow TAN to promote tumor growth and metastasis (Fridlender and Albelda, ; Pylaeva et al , ; Queen et al , ). Studies suggest that TANs have long life span due to chemokines and growth factor presence in the TME (Clappaert et al , ; Sawanobori et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, we found that an increased neutrophil numbers in cancer tissues are associated with aggressive tumors based on the state of differentiation of cancer tissues. TANs survive longer than circulating neutrophils that allow TAN to promote tumor growth and metastasis (Fridlender and Albelda, 2012;Pylaeva et al, 2016;Queen et al, 2005). Studies suggest that TANs have long life span due to chemokines and growth factor presence in the TME (Clappaert et al, 2018;Sawanobori et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation